Penetapan Harga Jual pada Agribisnis Ayam Petelur Sumber Bungur dengan Metode Full Costing berdasarkan Teori Penetapan Harga dalam Islam - Romli, Mohammad; Syahril Shobirin, Moch (Bulletin of Community Engagement, 2023)
This research aims to determine price determination in the Sumber Bungur Laying Chicken Agribusiness in terms of the full costing method and price setting theory in Islamic economics. This research uses a quantitative descriptive research approach using interview, observation and documentation techniques. Price determination for the Sumber Bungur Laying Chicken Agribusiness is carried out by calculating the cost of production (HPP) using the full costing method, which uses markup pricing. Determining HPP is done by adding up raw material costs, direct labor costs, variable factory overhead costs, and fixed factory overhead costs. Apart from that, the selling price determination at the Sumber Bungur Laying Chicken Agribusiness is in accordance with the principles of price setting in Islamic economics, related to fairness, justice, and adjustment to conditions of supply and demand in the market. Keywords: Islamic Price Determination, Determining Selling Prices, Chicken Agribusiness